YIELD OF IRRIGATED CABBAGE SUBMITTED TO DIFFERENT SOURCES AND DOSES OF BORON - Leão Junior, Laidson Alves; Buso, Wilian Henrique Diniz (REVISTA DE AGRICULTURA NEOTROPICAL, 2020)
Cabbage is an important vegetable for food. The use of micronutrients, more specifically boron, is important for plant development and head formation. The study aimed to evaluate the agronomic performance and yield of the cabbage crop submitted to the application of different sources and doses of boron. The study was carried out in the Água Verde farm, located in Nova Glória-GO, under irrigation by a center pivot system. The soil tillage consisted of operation with a subsoiler and a disk harrow. The fertilization was carried out by applying 48 kg ha-1 of N, 360 kg ha-1 of P2O5, and 120 kg ha-1 of K2O, in the planting furrow. The seedling transplant took place on 06/22/2019. At 20 days after transplanting, topdressing fertilization was carried out, with 200 kg ha-1 of N and 200 ha-1 of K2O. A randomized block design with four replications in a 4x5 factorial scheme was used. Four boron sources (boric acid, borax, ulexite, and Sulforgan) and five boron doses (0.0, 0.5, 1.0, 2.0, and 3.0 kg ha-1) were evaluated. Each experimental plot consisted of four rows of five meters in length. The evaluations were carried out on the two central rows, with 0.50 m at each end. The variables analyzed were plant height, longitudinal diameter, transverse diameter, number of outer leaves, and yield (kg ha-1). There was no significant difference between the different boron sources evaluated. For the different boron doses applied, only the number of outer leaves did not obtain a significant regression. The application of boron at a dose of 1.8 kg ha-1 resulted in the highest cabbage-head yield, totaling 82.58 t ha-1.